Enhancement in Lubricating, Rheological, and Filtration Properties of Unweighted Water-Based Mud Using XC Polymer NPs (Journal of Engineering, 2019)
In this research, an enhancement in lubricating, rheological, and filtration properties of unweighted water-based mud is fundamentally investigated using XC polymer NPs with 0.2gm, 0.5gm, 1gm, 2gm, and 4gm concentrations. Bentonite, that had been used in the preparation of unweighted water-based mud, was characterized using XRF-1800 Sequential X-ray Fluorescence Spectrometer, XRD-6100/7000 X-ray Diffractometer, and Malvern Mastersizer 2000 particle size analyzer, respectively. Lubricating, rheology and filtration properties of unweighted water-based mud were measured at room temperature (35°C) using OFITE EP and Lubricity Tester, OFITE Model 900 Viscometer, and OFITE Low-Pressure Filter Press, respectively. XC Polymer NPs show a good enhancement in lubricating, rheology and filtration properties of unweighted water-based mud. The effect of XC Polymer NPs on lubricating properties was denoted at 4gm concentration, where the reduction percentage in COF was 30%.  An increase in PV, YP, AV, gel strength of unweighted water-based mud was obtained due to the addition of XC Polymer NPs at concentrations up to 4gm. A reduction in filtrate volume and mud cake thickness of unweighted water-based mud was obtained due to the addition of XC Polymer NPs at 2gm and 4gm concentrations, the best result was obtained with using 4gm concentration, the reduction percentage of filtrate volume was 20.7% and mud cake thickness was 41%.